Treatment outcomes among children admitted stabilization centers in Eastern Ethiopia: retrospective study - Ahmed, Jemal Abrahim; Yusuf, Newas; Wilfong, Tara; Tukeni, Kedir Negesso; Berhanu, Hiwot; Roba, Kedir Teji (Frontiers in Public Health, 2023)
Background There is improved access to Sever Acute Malnutrition management in Ethiopia; however, studies have revealed an alarming rate of defaulters’ poor recovery and deaths, emphasizing the importance of researching to identify major causes. As a result, the goal of this research is to identify treatment outcome determinants and associated factors in severely malnourished children aged 6–59 months admitted to public hospitals in Eastern Ethiopia’s stabilization centers. Methods This study used an institutional-based retrospective cohort study design with 712 children aged 6 to 59 months. Data was gathered using a Sever Acute Malnutrition registration logbook and patient charts. Participants were chosen at random from their respective healthcare facilities based on population proportion. Epi-data was entered and analyzed using STATA version 14. To identify associated factors, the Cox proportional hazard Ratio was calculated, and a p-value of 0.05 at the 95% confidence interval was considered statistically significant. Results This study revealed that only 70.65% (95% CI = 67.19, 73.88) of the children were cured while 17.84% defaulted from the management and 5.90% died. Children who did not have tuberculosis (AHR = 1.58, 95%CI:1.04, 2.40), anemia (AHR = 1.31, 95% CI:1.03, 1.68), Kwash dermatosis (AHR = 1.41, 95%CI:1.04, 1.91), or on NG-tube (AHR = 1.71, 95%CI:1.41, 2.08) were more likely to be cured from SAM. Conclusion This study discovered that the cure rate is extremely low and the defaulter rate is extremely high. As a result, intervention modalities that address the identified factor are strongly recommended to accelerate the rate of recovery in Eastern Ethiopia.